Proceedings of the Proceedings of the 5th Annual International Seminar on Trends in Science and Science Education, AISTSSE 2018 2019
DOI: 10.4108/eai.18-10-2018.2287374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on Fresh Turmeric (Curcuma Longa L.) and Simplicia Toward Content of Curcumin Compound

Abstract: The effect of particle size of fresh turmeric and simplicia toward content of curcumin compounds has been carried out. The purpose of this research is to analyze the content of curcumin compounds based on the particle size of the fresh turmeric and simplicia using ethanol and water solvents. Extraction of curcumin in fresh turmeric and simplicia yield was carried out by maceration method of electrosynthetic coupling in etanol and water solvent using the infundation method, at particle sizes of 20, 80 and 140 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
Order By: Relevance
“…Thereby, the RWD was carried out until a constant sample weight could be achieved, at which the equilibrium moisture content (EMC) of the sample is attained. The dried samples were thereafter subjected to grinding using a dry portable electric blender and subsequent sieving using an 85 mesh sieve to obtain 0.180 mm particle size for the sieved samples (Daulay, Taufik, Ridwanto Syahputra, & Astriliana, 2019). Thereby, the powdered sieved sample was subjected to nutritional evaluations using analytical procedures summarized in the article.…”
Section: Methodsmentioning
confidence: 99%
“…Thereby, the RWD was carried out until a constant sample weight could be achieved, at which the equilibrium moisture content (EMC) of the sample is attained. The dried samples were thereafter subjected to grinding using a dry portable electric blender and subsequent sieving using an 85 mesh sieve to obtain 0.180 mm particle size for the sieved samples (Daulay, Taufik, Ridwanto Syahputra, & Astriliana, 2019). Thereby, the powdered sieved sample was subjected to nutritional evaluations using analytical procedures summarized in the article.…”
Section: Methodsmentioning
confidence: 99%
“…However, this method is affected by several different extraction parameters such as the amount of solvent, type of solvent, extraction time and particle size. Previous studies also reported that the extraction of bioactive compounds were greatly influenced by particle size of raw material [8], [9]. It was observed that with small particle size, most of the extraction was achieved when the powder was exposed to solvent and no further extraction occurred for a long period of time [8].…”
Section: Introductionmentioning
confidence: 98%
“…Daulay et al [9] reported that particle size affects the amount of extract produced in extraction process of bioactive compounds from plant materials. This is associated with the process of mass transfer from the plant matrix into solvent which occurs in two stages: The first stage is the process of penetration of the solvent into the plant matrix to dissolve the desired substance, and the second is the process of diffusion of the desired substance from inside the plant matrix to the extraction solvent.…”
Section: Introductionmentioning
confidence: 99%